2021
DOI: 10.3389/fbioe.2021.759303
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Starch Hydrogel/Contact Lens Composites as Epigallocatechin Gallate Delivery Systems for Inhibition of Bacterial Adhesion

Abstract: Microbial infections caused by wearing contact lenses has become a major health problem, so the design and development of antibacterial contact lenses has attracted widespread attention. To safely and effectively inhibit bacterial adhesion of contact lenses, we have facilely prepared epigallocatechin gallate (EGCG) loaded starch hydrogel/contact lens composites by in-situ free radical polymerization of the mixture containing 2-hydroxylethyl methacrylate, methacrylic acid and ethylene glycol dimethacrylate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The study found that the lenses induced minimal ocular irritation and allergic reactions, underlining the biocompatible nature of chitosan coatings. Similarly, research by Lee et al [47] investigated the biocompatibility of starch-based lens materials and found no adverse reactions, positioning them as safe alternatives for lens wearers.…”
Section: Biocompatibility For Safetymentioning
confidence: 97%
See 2 more Smart Citations
“…The study found that the lenses induced minimal ocular irritation and allergic reactions, underlining the biocompatible nature of chitosan coatings. Similarly, research by Lee et al [47] investigated the biocompatibility of starch-based lens materials and found no adverse reactions, positioning them as safe alternatives for lens wearers.…”
Section: Biocompatibility For Safetymentioning
confidence: 97%
“…Similarly, research by Lee et al. [ 47 ] investigated the biocompatibility of starch‐based lens materials and found no adverse reactions, positioning them as safe alternatives for lens wearers.…”
Section: Specific Examples and Studies Demonstrating Materials Proper...mentioning
confidence: 99%
See 1 more Smart Citation
“…The EGCG-loaded starch hydrogel/contact lens significantly reduced the adhesion ability of Pseudomonas aeruginosa and the material was non-toxic and degradable, providing a potential intervention strategy for the prevention of ocular microbial infections and suppression of bacterial keratitis. [252] Qin et al successfully prepared a 3D functionalized hydrogel similar to poplar plum using a glutinous corn starch/polyvinyl alcohol double cross-linked gel (W-Gel) backbone material by regeneration combined with freeze-thawing technique. The resulting hydrogel had excellent mechanical properties, and the hydrogel successfully adhered to soft and hard substrates such as skin, plastic, gauze, glass and metal for long-term and stable slow release of epigallocatechin gallate (EGCG), and the EGCG-loaded W-Gel showed good bactericidal ability in contact with Escherichia coli, Salmonella typhi, and Staphylococcus aureus and the surrounding environment.…”
Section: Biomedical Potential Of Natural Macromolecular Antibacterial...mentioning
confidence: 99%
“…The EGCG‐loaded starch hydrogel/contact lens significantly reduced the adhesion ability of Pseudomonas aeruginosa and the material was non‐toxic and degradable, providing a potential intervention strategy for the prevention of ocular microbial infections and suppression of bacterial keratitis. [ 252 ] Qin et al. successfully prepared a 3D functionalized hydrogel similar to poplar plum using a glutinous corn starch/polyvinyl alcohol double cross‐linked gel (W‐Gel) backbone material by regeneration combined with freeze‐thawing technique.…”
Section: Biomedical Potential Of Natural Molecular Antibacterial Hydr...mentioning
confidence: 99%